Comparison of Pregnancy Exercise and Depth Breath Relaxation for Lower Back Pain in Pregnant Women - Linda Chiuman (PRIMER (Prima Medical Journal), 2020)
The high number of LBP in the third trimester of pregnant women. A few numbers of study that explore the effect of pregnancy exercise and depth relaxation for LBP among pregnant women. This study was aimed to explore the efficacy of physical exercise and depth relaxation for reducing the severity of LBP. This study was an experimental study that used Pretest-Posttest Control Group Design among 28 third trimester of pregnant women in Royal Prima Hospital. The descriptive analysis, Mann-Whitney test, and Wilcoxon test were used to analyze the data. This study showed that at the initial observation time, there was no significant difference in the pain scale among the pregnant women. Meanwhile, at least two last observation time, there were significant differences in pain scale among each group of intervention and each observation time. Hence, pregnancy exercise is better than depth breath relaxation for reducing back pain severity after two weeks of intervention.